تعليم وتعلم اللغة الانجليزية في المرحلة الابتدائية بين المخاطرة والواقعية - جوزه عبدالله (University of Eloued جامعة الوادي, 2024)
ملخص: هدف الدراسة: هو الوقوف على درجة جدية وجاهزية وزارة التربية الوطنية في توفير متطلبات تدريس اللغة الانجليزية في المرحلة الابتدائية فيما يخص كل من المعلم والمتعلم والمادة الدراسية، وبيئة التعلم، والتي تعد مكونات العملية التعليمية. تحقيقا لهذا المقصد العلمي استعانت الدراسة بالمنهج الوصفي التحليلي من خلال تحليل الأدب النظري السابق حول التعليم العام، بالخصوص المتعلق بالمرحلة الابتدائية. نتائج الدراسة: بالمجمل توصلت الدراسة أن مختلف التحضيرات التي شرعت فيها الوزارة، مستعجلة وغير مدروسة بالشكل الكاف، وهو الأمر الذي سينبأ بمشكلات تعليمية كبرى للمعلمين الجدد، ويؤثر حتما على مستوى التحصيل اللغوي للتلاميذ. Abstract: The aim of the study is to determine the degree of the seriousness and readiness of the Ministry of National Education to provide the requirements for teaching English at the primary level with regard to the teacher, the learner, the subject and the learning environment, which are the components of the educational process. In order to achieve this scientific objective, the study used the descriptive analytical method through analysing previous theoretical literature on public education, especially those related to the primary stage. The results of the study in general, the study concluded that the various preparations initiated by the ministry are urgent and not sufficiently studied, which will predict major educational problems for new teachers, and inevitably the level of linguistic achievement of students.
قراءة أولية في التجربة الجزائرية أنموذج
Keywords: التعليم; التعلم; اللغة الانجليزية; المرحلة الابتدائية; المخاطرة; الواقعية; education; learning; English language; primary stage; risk; realism